Pengaruh Paparan Gas Ozon terhadap Jumlah Koloni Jamur Candida albicans - Chusaeni, Amana F.; Wibisono, Gunawan; Skripsa, Tira H. (Universitas Sam Ratulangi, 2021)
Abstract:Â Candida albicans is one of the pathogenic fungal species which causes oral infections. One of the methods to minimize the risk of fungal infection is by application of asepsis procedure through gargling with antiseptics. Ozone has high oxidative properties, therefore, it is considered as an antiseptic agent. Plasma Study Center of Diponegoro University has developed an ozone generator machine which opens up an opportunity to identify ozone properties as an antiseptic in controlling the number of fungal colonies, especially Candida albicans. This study was aimed to identify the effects of ozone exposure on the number of fungal colonies of Candida albicans. This was a laboratory experimental study with one-group pretest-posttest design. A total of 32 samples of Candida albicans suspensions were divided into two groups (16 each). Group 1 was not treated with ozonation, while group 2 were ozonated. Then, the two groups were cultured in SDA media using the spread plate method and were incubated for 48 hours. The data were obtained by calculating the number of fungal colonies growing in SDA media. The Wilcoxon test obtained a p-value <0.05, meaning that there were differences in the colony number of Candida albicans before and after ozonation. In conclusion, ozone exposure has a significant effect on the number of fungal colonies of Candida albicans. Further studies are needed adding variables or parameters. Keywords: ozone; fungal colony; Candida albicansÂ Â Abstrak: Candida albicans merupakan salah satu spesies jamur patogen yang menyebabkan infeksi oral. Salah satu metode untuk meminimalkan risiko infeksi jamur ialah melalui penerapan prosedur asepsis dengan berkumur menggunakan antiseptik. Ozon memiliki kemampuan oksidasi tinggi sehingga dipertimbangkan untuk menjadi bahan antiseptik. Pusat Penelitian Plasma Universitas Diponegoro telah mengembangkan mesin generator ozon yang membuka peluang untuk mengetahui kemampuan ozon sebagai antiseptik dalam mengendalikan jumlah koloni jamur terutama Candida albicans. Penelitian ini bertujuan untuk mengetahui adanya pengaruh paparan gas ozon terhadap jumlah koloni jamur (Candida albicans). Jenis penelitian ialah eksperimental laboratorik dengan one group pretest-posttest design. Sebanyak 32 sampel suspensi jamur Candida albicans dibagi menjadi dua kelompok (masing-masing 16 sampel). Kelompok 1 tidak dilakukan ozonasi dan kelompok 2 dilakukan ozonasi kemudian kedua kelompok dikultur dalam media SDA dengan metode spread plate dan diinkubasi 48 jam. Data diperoleh dengan menghitung jumlah koloni jamur yang tumbuh pada media SDA. Hasil uji statistik Wilcoxon mendapatkan nilai p<0,05 yang berarti terdapat perbedaan jumlah koloni jamur (Candida albicans) sebelum dan setelah pemberian gas ozon. Simpuolan penelitian ini ialah paparan gas ozon berpengaruh secara bermakna terhadap jumlah koloni jamur (Candida albicans). Penelitian lanjutan diperlukan dengan penambahan variabel atau parameter.Kata kunci: gas ozon; koloni jamur; Candida albicans